2015
DOI: 10.1016/j.molcel.2015.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Caspase-3 Promotes Genetic Instability and Carcinogenesis

Abstract: Summary Apoptosis is typically considered an anti-oncogenic process since caspase activation can promote the elimination of genetically unstable or damaged cells. We report that a central effector of apoptosis, caspase 3, facilitates, rather than suppresses, chemical and radiation-induced genetic instability and carcinogenesis. We found that a significant fraction of mammalian cells treated with ionizing radiation can survive, despite caspase 3 activation. Moreover, this sublethal activation of caspase 3 promo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
201
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 215 publications
(213 citation statements)
references
References 52 publications
8
201
0
4
Order By: Relevance
“…Recent data show that cells which initiate apoptosis but do not die -we term this failed-apoptosis-sustain potentially oncogenic damage such as genomic instability and gene amplification (Figure 3) [71][72][73] . The failure to commit suicide is puzzling given what we know about apoptosis.…”
Section: Failed Apoptosis and Cancermentioning
confidence: 99%
See 3 more Smart Citations
“…Recent data show that cells which initiate apoptosis but do not die -we term this failed-apoptosis-sustain potentially oncogenic damage such as genomic instability and gene amplification (Figure 3) [71][72][73] . The failure to commit suicide is puzzling given what we know about apoptosis.…”
Section: Failed Apoptosis and Cancermentioning
confidence: 99%
“…Finally, the level of caspase activity that is required to kill a cell does not appear to be very high 76 . These points notwithstanding, various studies have found that cells can engage caspase activity and survive, sustaining damage in the process [71][72][73]70 Intense interest has surrounded the potential of TRAIL ligands as anticancer therapies because many tumour-types are selectively sensitive to TRAIL-mediated apoptosis 77 . One of the first studies that demonstrated engagement of caspases activity in the absence of cell death focused on TRAIL-induced apoptosis 78 .…”
Section: Failed Apoptosis and Cancermentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, surviving doses of TRAIL provokes mutagenesis through caspase-8 activation. In a more recent study, Liu et al (2015) showed that sublethal activation of caspase-3, after exposure to ionizing radiation, leads to genomic instability, oncogenic transformation, and increased tumorigenic nature in MCF10A mammalian cells, and the downstream effector of caspase-3 is EndoG in this damage. Absence of caspase-3 reduced these alterations.…”
Section: Caspases In Tumor Cell Repopulation and Motilitymentioning
confidence: 99%